2017
DOI: 10.1093/neuros/nyx153
|View full text |Cite
|
Sign up to set email alerts
|

Establishing Minimal Clinically Important Difference of Spinal Cord Stimulation Therapy in Post-Laminectomy Syndrome

Abstract: The MCID for SCS placement was calculated using 4 different methods. The results are similar to calculations for the MCID for many lumbar and cervical procedures done for pain. Our results suggest that an improvement of 1.2 to 3.7 points on the VAS scale and 8.2 to 13.3 points on the ODI is clinically meaningful to the patient. Further defining the MCID for SCS therapy will remain of utmost importance in order to justify the cost of the procedure.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
35
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 33 publications
(38 citation statements)
references
References 18 publications
2
35
1
Order By: Relevance
“…The pooled analysis showed that the average pooled pain score with tonic SCS was 49.2, whereas with burst SCS it was 36.7, a 12.5-point difference. This is likely to be experienced by the subjects as a clinically important difference, given that the minimal clinically important difference (MCID) for multidisciplinary pain treatment for low back pain was 1 point on a 0–10 NRS [40] and the MCID for SCS treatment of postlaminectomy syndrome was 1–1.2 cm on a 10-cm VAS [41]. The clinical importance of the incremental benefit of burst was supported by the large majority of subjects who preferred burst SCS over tonic.…”
Section: Discussionmentioning
confidence: 99%
“…The pooled analysis showed that the average pooled pain score with tonic SCS was 49.2, whereas with burst SCS it was 36.7, a 12.5-point difference. This is likely to be experienced by the subjects as a clinically important difference, given that the minimal clinically important difference (MCID) for multidisciplinary pain treatment for low back pain was 1 point on a 0–10 NRS [40] and the MCID for SCS treatment of postlaminectomy syndrome was 1–1.2 cm on a 10-cm VAS [41]. The clinical importance of the incremental benefit of burst was supported by the large majority of subjects who preferred burst SCS over tonic.…”
Section: Discussionmentioning
confidence: 99%
“…Thus, the use of the PETSCSC may significantly improve holistic care of SCS patients. Additionally, improvement of patient selection tools may help eliminate the patients in our cohort who, at latest follow‐up, would not repeat surgery and thus limit healthcare expenditures .…”
Section: Discussionmentioning
confidence: 99%
“…This degree of pain relief is in line with other reports of the effectiveness of DRG stimulation . It is likely that this degree of pain relief was interpreted by patients as a significant improvement, as it greatly exceeds the minimal clinically important difference for pain ratings .…”
Section: Discussionmentioning
confidence: 99%